Dispute resolution through conciliation and its contributions to extrajudicial litigants (Research, Society and Development, 2022)
Conciliatory procedures have existed since the dawn of humanity by primitive methods corresponding to that time. Over time, more civilized ways were used successfully in settling disputes between clans, family conflicts, and in settling commercial differences. The objective is to discuss the extrajudicial resolution of conflicts through conciliation through the Brazilian legal system. The study is based on the bibliographic research of the literature in online databases of studies published between the years 2014 to 2021 with the descriptors: mediation, conciliation, arbitration, Law 13.140/2015, Code of Civil Procedure. Studies indicate that one of the forms of extrajudicial dispute resolution is expressed both in Law 13.140/2015 and in the Civil Procedure Code (Law n. 13.105/15) which emphasize medication and conciliation as ways of pacifying conflicting interests extrajudicially between the parties involved through a third party as a means.